Shark derivatives (Alkylglycerols, Squalene, Cartilage) as putative nutraceuticals in oncology - Vadalà, Maria; Laurino, Carmen; Palmieri, Lucia; Palmieri, Beniamino (European Journal of Oncology and Environmental Health, 2017)
The capability of sharks to resist infection and the low incidence of tumors found in different species of sharks (e.g. spiny dogfish shark, tiger shark) suggested the presence into their tissues of active compounds, provided of anticancer activities, such as Alkylglycerols (from the shark liver), Squalene (from the shark mesenchyme and skin), and Cartilage (from the shark skeleton). The Alkylglycerols, highly concentrated in the shark liver oil, have several biological activities: stimulation of hematopoiesis, immune-modulation, anti-tumors. The Squalene is an anticancer, antioxidant, detoxifier, skin hydrating, drug carrier and emollient agent. The Cartilage has anti-inflammatory properties commonly used in the folk medicine for the treatment of arthritis, osteoarthritis, diabetic retinopathy, psoriasis, and supposedly also anticancer.